Reinforcement of the State's Role and Professionalization of Public Service: An Analysis of Digital Transformation in Public Services Through the Innovation of the Online Administrative Services Information System (SIOLA) at the Ministry of Home Affairs - Herdiani Narita Pricillia; Bintoro Wardiyanto; Erna Setijaningrum (Jurnal Impresi Indonesia, 2025)
Public service innovation through the Online Administrative Services Information System (SIOLA), developed by the Ministry of Home Affairs (Kemendagri), represents a strategic effort to modernize public administration by promoting efficiency, transparency, and accountability in service delivery. SIOLA is designed to integrate various administrative services into a unified digital platform, enabling online submission, monitoring, and evaluation of administrative processes while reducing bureaucratic complexity and service delays. This study aims to analyze the role of SIOLA in transforming public service governance within the Ministry of Home Affairs and to assess its alignment with contemporary public administration paradigms. The research employs a qualitative descriptive approach, utilizing secondary data obtained from academic articles, official government reports, policy documents, and relevant literature. The findings indicate that SIOLA has significantly improved administrative efficiency, enhanced transparency through traceable service processes, and strengthened accountability by providing measurable performance indicators. Moreover, SIOLA supports the broader agenda of digital bureaucracy transformation by reinforcing standardized procedures and professional work mechanisms within public institutions. From a theoretical perspective, the implementation of SIOLA reflects the principles of the Neo-Weberian State, particularly the strengthening of the state’s coordinating role, the professionalization of public services, and the integration of managerial efficiency with legal-rational authority. Despite its positive impacts, the study also highlights challenges related to technological readiness and human resource capacity. Overall, SIOLA demonstrates substantial potential as a model of digital public service innovation for other government institutions.